2006
DOI: 10.1177/0961000606060957
|View full text |Cite
|
Sign up to set email alerts
|

Library media program implementation and student achievement

Abstract: This study examines possible factors related to school library programs that correlate with student academic achievement. Analyzing library programs as a system, the investigator adapted the American Association of School Librarians (AASL) principles for library media programs in conjunction with standardized tests. For the population examined (60 southern California schools), the measure that correlated most closely with library program principles was standardized reading scores. Specifically, the degree to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…The study found that test scores rise as library media specialists spend more time collaborating with teachers when planning information literacy lessons, identifying materials, teaching information literacy skills to students and providing inservice training to teachers. These results are consistent with those of Farmer (2006), who examined key indicators within school library programmes at 60 schools ranging from the elementary school level to the high school level. The results revealed that collaborative planning between teachers, administrators and professional library staff was the most significant factor (.853) in a school library programme to impact student academic success on state standardized achievement tests.…”
Section: 22 Benefits Of Teacher and Librarian Partnershipssupporting
confidence: 90%
See 1 more Smart Citation
“…The study found that test scores rise as library media specialists spend more time collaborating with teachers when planning information literacy lessons, identifying materials, teaching information literacy skills to students and providing inservice training to teachers. These results are consistent with those of Farmer (2006), who examined key indicators within school library programmes at 60 schools ranging from the elementary school level to the high school level. The results revealed that collaborative planning between teachers, administrators and professional library staff was the most significant factor (.853) in a school library programme to impact student academic success on state standardized achievement tests.…”
Section: 22 Benefits Of Teacher and Librarian Partnershipssupporting
confidence: 90%
“…(Montiel-Overall, 2008, p. 150) As the quote above illustrates, Montiel-Overall emphasises that to improve students' learning, school librarians need to be an integrated part of instruction and evaluation practices at a school. Farmer, 2006;Hartzell, 2002). The fifth and last theme focuses on factors that create the motivation to collaborate.…”
Section: Low Highmentioning
confidence: 99%
“…Stone and Ramsden reported that much of the current research has been around school library resources (Farmer, 2006, Ontario Library Association, 2006. There have been a number of recent studies looking at academic library value and researchers (Auckland, 2012, Oakleaf, 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent literature reviews looking into library usage and undergraduate attainment have found little evidence of research until the last few years (Cox and Jantti, 2012;. Stone and Ramsden reported that much of the current research has been around school library resources (Farmer, 2006;Ontario Library Association, 2006). There have been a number of recent studies looking at academic library value and researchers (Auckland, 2012;Oakleaf, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vent (2006) concluded in his study that results of students" summative evaluation are based on student"s visits and consultation of books. Farmer (2006) concluded that libraries closely interferes students" academic achievement.…”
Section: Introductionmentioning
confidence: 99%